The role of Aha1 in cancer and neurodegeneration - Blagg, Brian S.J.; Catalfano, Kevin C. (Frontiers in Molecular Neuroscience, 2024)
The 90 kDa Heat shock protein (Hsp90) is a family of ubiquitously expressed molecular chaperones responsible for the stabilization and maturation of >400 client proteins. Hsp90 exhibits dramatic conformational changes to accomplish this, which are regulated by partner proteins termed co-chaperones. One of these co-chaperones is called the activator or Hsp90 ATPase activity homolog 1 (Aha1) and is the most potent accelerator of Hsp90 ATPase activity. In conditions where Aha1 levels are dysregulated including cystic fibrosis, cancer and neurodegeneration, Hsp90 mediated client maturation is disrupted. Accumulating evidence has demonstrated that many disease states exhibit large hetero-protein complexes with Hsp90 as the center. Many of these include Aha1, where increased Aha1 levels drive disease states forward. One strategy to block these effects is to design small molecule disruptors of the Hsp90/Aha1 complex. Studies have demonstrated that current Hsp90/Aha1 small molecule disruptors are effective in both models for cancer and neurodegeration.